Cutaneous immune‐related adverse events in patients with melanoma treated with checkpoint inhibitors. (1st February 2021) - Gault, A.; Anderson, A.E.; Plummer, R.; Stewart, C.; Pratt, A.G.; Rajan, N.
Summary: Checkpoint inhibitor (CPI) therapy has vastly improved long‐term outcomes in metastatic malignant melanoma (MMM). Therapy takes the form of monoclonal antibody infusions that target immune cell checkpoint proteins, such as cytotoxic T‐lymphocyte‐associated protein 4 (CTLA4) and programmed death 1/programmed death ligand 1 (PD1/PDL1). Cutaneous immune‐related adverse effects (IrAEs) are frequent in patients with MMM treated with CPIs. Our aim was to review the clinical presentations of cutaneous IrAEs associated with CPI therapy in adult patients with MMM. We carried out a literature review of clinical trials, case series and case reports of patients with melanoma and those with other cancers treated with anti‐CTLA4, anti‐PD1/PDL1, or a combination of these therapies. Diverse clinical presentations of cutaneous IrAEs are recognized. Anti‐CTLA4 therapy has a higher associated rate of cutaneous IrAEs than anti‐PD1/PDL1 therapies. Low‐grade cutaneous IrAEs are common and are usually managed supportively while continuing CPI therapy. Delayed presentations arising after established use of CPIs can make therapy‐associated cutaneous IrAEs difficult to distinguish from coincidental dermatological disease. Vitiligo‐like depigmentation is a good prognostic indicator of outcome in patients with melanoma. Life‐threatening adverse events including toxic epidermal necrolysis are rare. The identification of predictive biomarkers that highlight patients at risk of life‐threatening IrAEs remains an unmet need. The involvement of dermatologists in the multidisciplinary assessment of cutaneous IrAEs is increasingly pertinent in the management and care of CPI‐treated patients with melanoma.